Perceptions of Students of English Education Program towards ICT in ELT Course - Nugrahani, Arina (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
There has been a considerable number of studies related to the use of ICT in English as a Foreign Language (EFL) context. However, only a limited amount of research that examines the practice of ICT teaching and learning to EFL students has been conducted. Hence, this study intends to address this issue. Specifically, it aims to investigate the perception of students of English Education Program towards ICT in ELT course. This research applies qualitative approach with case study research design. The data were collected from observation in ICT in ELT course in Brawijaya University and there were three classes being observed. In addition, interviews with students were also conducted. The study employs purposive sampling, and from each class, three participants were selected based on recommendation from the instructors. A total of 9 students were then chosen as the participants in this study. The research findings show that all the research participants agree that it is important for English Education students to learn ICT. Furthermore, related to their preference in ICT teaching method, 44% of the respondents argued that online learning is better while the other 56% prefers offline face-to-face meeting. Finally, it is found that all of the respondents have positive perceptions about the ICT course. The ICT course was depicted as fun and necessary, important, exciting, helpful, and useful.